Breaking Down Gender Stereotypes: Analyzing the Meaning of Equality in ABC Soy Sauce Advertisements - Manna Maria Sopiana Manalu; Sulis Triyono (Britain International for Academic Research (BIAR) Publisher, 2024)
Social media is one of the most common tools and we can get any information we need, for example about gender equality. One of the social media hits right now is YouTube. YouTube can search for various information and even place advertisements to sell. To unlock the wrong thinking towards women’s equality. This research uses Fairclough's critical discourse analysis method and Derrida's deconstruction theory. The results showed that in the ABC soy sauce advert, there is gender inequality between women and men where men must always be served. Men assume that a woman's job is only in the kitchen and taking care of housework. This ABC Soy Sauce advert plays an important role in breaking down gender stereotypes by presenting a more inclusive and balanced picture of the roles of men and women in everyday life. By dissecting the meaning behind the advert, the author highlights the importance of promoting equality and dismantling traditional gender norms. The findings suggest that the Kecap ABC advert has the potential to challenge stereotypes and promote a more inclusive society.